Child-Gendered Mental Spaces Triggered by Space Builders Reflect Art Psychotherapy Clients' Childhood Experiences - Nilasari, Nindita; Hardjanto, Tofan Dwi; Handayani, Wiwik Retno (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2023)
ABSTRACT The language behaviour of clients’ reflection journey on art psychotherapy in the final stage of art psychotherapy sessions entitled ‘Reflect Interview’ reflects their childhood experiences that become a lifetime memory. In this paper, the topic of how the clients can construct their conceptual ideas of childhood experiences is discussed under a cognitive approach to language study. This article argues that: 1) There are REFLECTION SPACE, REALITY SPACE, DEPICTION SPACE and POSSIBILITY SPACE of the child-gendered mental spaces in the reflection journey on art psychotherapy, 2) Subject-Verb combinations, connectives and adverbs as the space builder on the child-gendered mental spaces and 3) Intersection between gender and child has experienced by the psychotherapy clients are generally related to weakness, depression, struggle and difficulties that become children's memories during their lifetime. These results are supported by a few background cases and government role illustrations in Indonesia. Keywords: Art psychotherapy; child-gendered mental spaces; space builder.